Efficacy of Silymarin on Aflatoxin Residues in Eggs and Health Status of Laying Hens - Hussein Ali Rashid1 , Mushtaq Talib Abdulwahid2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study aimed to evaluate the silymarin in reducing the aflatoxin (AF) residues in eggs and health status of laying hens. A total of 120 laying hensat the age of 240 days were randomly divided into three equal groups fed on diet with or without AF and 0.5% of silymarin. The residues of AF in the eggs were measured at the age of 260 and 280 days by using HPLC technique as well as, physiological tests. The results of the 3rd group showed a significant (P?0.05) increase in RBCs, PCV% and Hb, AST, ALT concentrations and Ab titer against ND and IB diseases as compared with the 2nd group and the control. Also, there was a significant (P?0.05) decrease in the concentrations of AF (B1) and (G1) in eggs at the age of 260 days as compared with the 2nd and the control